Field Effect Passivation in Perovskite Solar Cells by a LiF Interlayer - Menzel, D.; Al-Ashouri, A.; Tejada, A.; Levine, I.; Guerra Torres, J.A.; Rech, B.; Albrecht, S.; Korte, L. (John Wiley and Sons, 2022)
The fullerene C₆₀ is commonly applied as the electron transport layer in highefficiency metal halide perovskite solar cells and has been found to limit their open circuit voltage. Through ultra-sensitive near-UV photoelectron spectroscopy in constant final state mode (CFSYS), with an unusually high probing depth of 5–10 nm, the perovskite/C₆₀ interface energetics and defect formation is investigated. It is demonstrated how to consistently determine the energy level alignment by CFSYS and avoid misinterpretations by accounting for the measurement-induced surface photovoltage in photoactive layer stacks. The energetic offset between the perovskite valence band maximum and the C₆₀ HOMO-edge is directly determined to be 0.55 eV. Furthermore, the voltaje enhancement upon the incorporation of a LiF interlayer at the interface can be attributed to originate from a mild dipole effect and probably the presence of fixed charges, both reducing the hole concentration in the vicinity of the perovskite/C₆₀ interface. This yields a field effect passivation, which overcompensates the observed enhanced defect density in the first monolayers of C₆₀.
Keywords: Passivation; Materials science; Perovskite (structure); X-ray photoelectron spectroscopy; Monolayer; Open-circuit voltage; Halide; Analytical Chemistry (journal); Photoemission spectroscopy; Optoelectronics; Layer (electronics); Chemical engineering; Voltage; Inorganic chemistry; Nanotechnology; https://purl.org/pe-repo/ocde/ford#2.04.00